Rago, Kingman County - Levin, Ethan (Kansas State University, The Chapman Center for Rural Studies, 2019)
Rago, KS is the home of aviation pioneer, Clyde Cessna. Though the home of someone who was so important to the history of air travel, the town now sits in a state of dilapidation and decay. This essay discusses the history of Rago, and the events that led it to where it is today.
Ethan Levin, “Rago, Kingman County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/209.
Keywords: Cessna Homestead; Clyde Cessna; history; Kansas; Kingman County; Rago